PENGARUH STRATEGI PEMBELAJARAN PHYSICAL SELF ASSESSMENT BERBASIS JOYFULL LEARNING TERHADAP HASIL BELAJAR SISWA KELAS XI IPA SMA NEGERI 5 BANJARMASIN PADA MATERI LARUTAN PENYANGGA - Putry Dessy Primia K; Abdul Hamid (Universitas Lambung Mangkurat, 2015)
Abstract: Research has been done about the influence of learning strategy Physical Self-Assessment (PSA) based Joyfull Learning the student learning outcomes at class XI science SMA Negeri 5 Banjarmasin on material buffer solution the school year 2013/2014. The aims of this research are (1) to know differences in student learning outcomes in strategy of PSA based Joyfull Learning between macromedia flash media, internet media, and conventional learning, and (2) to know students’response toward the strategy of PSA based Joyfull Learning on material of buffer solution. This research uses a quasiexperimental methods with nonequivalent control group design. Population are student of class XI science SMAN 5 Banjarmasin, and sample is class XI IPA 1, XI IPA 2, XI IPA 3 determined by cluster random sampling. Instrument of collecting data are test and questionnaire. Than datas were analyzed by normality test, homogeneity test, Anava 1 Jalur test, and Duncan test. This research show that (1) there are differences in learning outcomes between student at class experiment with PSA strategies based Joyfull Learning and student at class control with conventional learning, (2) Joli test and Duncan test prove that PSA strategies based Joyfull Learning better than conventional learning, (3) N-Gain prove that in learning outcomes student with PSA strategies based Joyfull Learning higher than student with conventional learning, and (4) students gave a positive response to PSA strategies based Joyfull Learning on material of buffer solution.Keywords: Physical Self-Assessment, Joyfull Learning, Buffer solution